Obra e instanciações na organização da informação musical: estudo da adequação do modelo conceitual FRBR - Katia Lucia Pacheco (2016)
This research aims at exploring the theme music bibliographic universe, and limits to the understanding of the work organization and its instantiations in the organization of musical information, under the bias of the premises of the conceptual model of FRBR and the philosophy of music speech input on the notion of work. It is intended to establish connections between these discourses in order to find attributes and settings that contribute to the production of knowledge about the organization of musical information and provide subsidies to improve the practice of bibliographic representation of musical documents in information retrieval systems. The object of study is the organization of information regarding the musical work and bibliographic relations of its instantiations. The discussion about the nature of the musical work under the rule of Music, in the philosophical and musicological field, although theoretical, has direct relevance to the practices of cataloging activities of musical documents and also the potential to improve the practice of creating bibliographic records. The research associates also the prospect of understanding the intent of bibliographic activities related to a musical work and its importance for the chain of information and the description of musical documents. This qualitative research will cover procedures descriptive in nature and will employ also the type empirical research. It was shaped to take place in two stages. The first step is based entirely on literature of Brazilian and foreign documents of interest in the area, for the establishment of the theoretical research framework and state of the art of applying FRBR model. The second stage proposes using the Discovery System Music Scherzo, Product Variations / FRBR project: Variations as a Tested for the FRBR Conceptual Model of the University of Indiana in the United States for analysis of bibliographic relationships between musical works and their instantiations. The approaches on the conceptualization of musical work, both on the part of the authors who examined the theme from the point of view of the ontology and the musical analysis, and from the authors who considered the work under the bias of the information retrieval, pointed to the ambiguity in Definition of the term and the difficulty of elaborating a definition that takes into account the varieties of instantiations of the musical work, addressing at the same time the multiple dimensions of written notation, live performance and recorded sound. The results showed that the Scherzo System is not yet designed to accommodate all structures of bibliographic relations and complex sets of emerging entities of the FRBR model, through a graphic display.